Lithium-induced outcome devaluation in instrumental conditioning: Dose–effect analysis - PAREDES-OLAY, Concepcion; LOPEZ, Matias (Physiology & behavior, 2002)
Three experiments with rats assessed the effectiveness of various doses of lithium chloride (LiCl) in producing an aversion to the reinforcer on subsequent instrumental performance in extinction. In Experiments 1A and 1B, subjects were injected with LiCl at a dose of 3.0 and 1.5 meq/kg, respectively. These doses were administered in the form of either an isotonic solution (0.15 M) or a hypertonic solution (0.6 M). While there was an effect of the reinforcer devaluation on the instrumental performance that did not depend on the molarity of the solution with the high LiCl dose, there was no effect of devaluation with the low LiCl dose. Experiment 2 compared the 3.0- and 1.5-meq/kg dose levels directly. A depression of instrumental performance after outcome devaluation was observed in the animals injected with the high LiCl dose independently of the molarity of the solution, an effect that was absent in the low-dose condition. These results were interpreted as evidence that an instrumental reinforcer devaluation effect induced by pairing the reinforcer with illness depends upon the absolute quantity of LiCl injected and not on the concentration of solution.